Livestock to 2020: the next food revolution [in Japanese] - Delgado, Christopher L.; Rosegrant, Mark W.; Steinfeld, Henning; Ehui, Simeon; Courbois, Claude (International Food Policy Research Institute, 2001)
A team of researchers from the International Food Policy Research Institute (IFPRI), the Food and Agricultural Organization of the United Nations (FAO), and the International Livestock Research Institute (ILRI) collaborated to produce this comprehensive and even-handed attempt at defining the nature, extent, scope, and implications of what they term the "Live stock Revolution in developing countries. Looking forward to 2020, they argue convincingly that the structural shifts in world agriculture being brought about by shifts in developing-country demand for foods of animal origin will continue and that increasingly global markets have the ability to supply both cereal and animal products in desired quantities without undue price rises. They emphasize, however, that policy decisions taken for the livestock sector of developing countries will determine whether the Livestock Revolution helps or harms the world s poor and malnourished. The report emphasizes the importance of continued investment in both research on and development of animal and feed grain production and processing, and the need for policy action to help small, poor livestock producers become better integrated with commercial livestock marketing and processing. It details a host of requirements in the area of technology development for production and processing of livestock products, potential benefits from new technologies, and critical policy issues for environmental conservation and protection of public health.